The Mud and the Water: Towards a History of a Simile in Kabbalah. - Idel, Moshe (Zutot: Perspectives on Jewish Culture, 2017)
The present study surveys a series of kabbalistic antecedents of a simile for the presence of the roots of evil in the pre-emanationalist stage, as formulated in Lurianic Kabbalah. What has been conceived by scholars as a cathartic explanation characteristic of Lurianism, and even an esoteric aspect of this Kabbalah, turns to be quite an exoteric teaching shared by several kabbalists since the 13th century